O TRABALHADOR INFORMAL NOS ÔNIBUS: uma das faces da questão urbana na Região Metropolitana de Belém/RMB - Christiane Pimentel e Silva; João Paulo Gois Alves (Revista de Políticas Públicas, 2008)
The process of space occupation in the Brazilian ́s city of Belém metropolitan area occurred in unequal ways, following the different nature of the local production, segregating a great part of the population to the poorest or peripheral areas. The capitalist conditions of contemporaries ́ production have contributed for an increase of the informal work market, hat ends up submitting itself to the logic of the market. Considering the informal confusing city areas ́ occupation it was chosen to observe the ambulant workers in the buses, who occupy a flexible work environment.